Media Tangga Konversi Berbantuan Lagu Untuk Meningkatkan Hasil Belajar Matematika - Leni Fitriyani (Journal of Elementary Education Research, 2022)
The understanding of the concept of unit length conversion in 3rd grade students of SDIT Al Akhyar is still relatively low. This can be seen from the percentage of completeness which is only 24%. For this reason, it is necessary to improve learning. The first step that was chosen was to use the Length unit Conversion ladder media. The purpose of this study was to improve student achievement in learning Mathematics for length unit conversion material using the Conversion Ladder media. This research is a classroom action research conducted at SDIT Al Akhyar. This research went through two cycles. The research phase of each cycle is carried out starting from planning, implementation, observation, data collection, and reflection. The results of the implementation are evaluated in the reflection as the basis for improvement plans in the next cycle. Data analysis used qualitative and quantitative analysis. The results showed an increase in students' ability to convert length units from pre-cycle, cycle 1 and cycle 2. The average value in pre-cycle was only 53.10, cycle 1 increased to 68.96 and cycle 2 became 88.27. The percentage of completeness of students increased from 24% or 7 students who experienced completeness in the pre-cycle, to 55% (16 students) in cycle 1 and 83% or 24 students who completed learning in cycle 2. These findings indicate that the use of ladder media conversion can improve learning outcomes in learning Mathematics in the length unit material.